Познаю мир: для детей 4-5 лет (В. А. Егупова) - Егупова Валентина Александровна (Ломоносовская школа, 2016)
Экземпляры: Ф-21; Ф-22; Ф-23; Ф-24 (20161010) / Инвентарный номер: 92045 / Цена: / Авт.знак: Е31 / ББК: 74.102